2020
DOI: 10.1021/acs.jced.0c00739
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Measurement of Carbon Dioxide Solubility in Aqueous N-Methyldiethanolamine + 2-(2-Aminoethylamino) Ethanol + Sulfolane and Diethanolamine + 2-(2-Aminoethylamino) Ethanol + Sulfolane Hybrid Solvents at Various Temperatures and High Pressure

Abstract: The sets of vapor–liquid equilibrium (VLE) data for CO2 solubility in a combination of (N-methyldiethanolamine (MDEA) + 2-(2-aminoethylamino) ethanol (AEEA)) and (diethanolamine (DEA) + AEEA) as a chemical solvent blended with sulfolane as a physical solvent are acquired at 313.15–343.15 K within the CO2 partial pressure range up to 5600 kPa. The measurements are fulfilled for two different hybrid solvents of MDEA + AEEA + sulfolane with the weight compositions of (20–10–10) wt % and (20–10–20) wt % and a mixe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…We attached a calibrated thermocouple (model ST-612, Standard Instrument Co. Ltd., Hong Kong) to this gas-storage vessel to display its temperature accuracy of ±0.1 K. Moreover, to determine the pressure, we equipped the injection cell with the same 0–10,000 kPa calibrated pressure transducer (model 33X, Keller, Switzerland) with uncertainties of 1.75 kPa. It should be mentioned that the manufacturers of these measurement tools have quantified the various instruments’ precisions of the present setup . Moreover, a vacuum pump (model DV-142 N-PLATINUM 5 CFM, JB Company, USA) was used for the equilibrium high-pressure cell’s depletion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We attached a calibrated thermocouple (model ST-612, Standard Instrument Co. Ltd., Hong Kong) to this gas-storage vessel to display its temperature accuracy of ±0.1 K. Moreover, to determine the pressure, we equipped the injection cell with the same 0–10,000 kPa calibrated pressure transducer (model 33X, Keller, Switzerland) with uncertainties of 1.75 kPa. It should be mentioned that the manufacturers of these measurement tools have quantified the various instruments’ precisions of the present setup . Moreover, a vacuum pump (model DV-142 N-PLATINUM 5 CFM, JB Company, USA) was used for the equilibrium high-pressure cell’s depletion.…”
Section: Methodsmentioning
confidence: 99%
“…It should be mentioned that the manufacturers of these measurement tools have quantified the various instruments' precisions of the present setup. 31 Moreover, a vacuum pump (model DV-142 N-PLATINUM 5 CFM, JB Company, USA) was used for the equilibrium high-pressure cell's depletion. This apparatus is connected to a CO 2 cylinder for charging gas to the injection cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Idem et al stated that the energy consumed for solvent regeneration in an MDEA/MEA hybrid system was less than that consumed by an MEA system . In addition, there have been many works examining CO 2 solubility and its equilibrium in TEA and MDEA systems at various temperatures and CO 2 partial pressures, and most of them primarily focused on increasing the overall CO 2 absorption performance of the systems. However, no studies have reported the quantitative individual amount of CO 2 chemically absorbed by amine and physically absorbed by water relative to the total absorption capacity, which can be calculated in TEA and MDEA systems.…”
Section: Introductionmentioning
confidence: 99%